ANTITRUST REGULATION IN TERMS OF ENTERPRISE DEVELOPMENT CHLOR-ALKALI INDUSTRY - N. N. Grinyov (Модернизация, инновация, развитие, 2015)
The article reveals the problems of antitrust regulation activities of processing enterprises. The necessity of improving the activity of enforcement to prevent the emergence of monopolistic market structures chlor-alkali industry.